Pempek: Traditional fishcake dish from South Sumatra, Indonesia - Reggie Surya; Welsen Destifen; David Nugroho; Stephanie (jurnal1, 2023)
Pempek is a traditional fishcake dish from South Sumatra, Indonesia. Its primary ingredients are narrow-barred Spanish mackerel (Scomberomorus commerson) and sago starch. As a dish, Pempek is usually served with a sweet and sour sauce called kuah cuko, containing palm sugar, vinegar, tamarind, and chili pepper. Historically, Pempek is highly influenced by Chinese cuisine.Pempek exists in different varieties, most of which are widely known and available in many Indonesian cities. The variation among different types of Pempek appears due to different additional ingredient, shape, filling, cooking method, and serving style. Some well-known types of Pempek include Pempek adaan (round shaped), Pempek lenjer (cylindrical shaped), Pempek kapal selam (egg stuffed), Pempek keriting (curly shaped), and Pempek kulit (made with fish skin). New innovations on Pempek recipe are also thriving owing to people’s creativity. The popularity of Pempek has made this dish the symbol of identity and pride for the people of South Sumatra. It is also rich in historical and philosophical values that represent the South Sumatran traditional way of life. In addition, Pempek is currently considered to be an Intangible Cultural Heritage by the UNESCO. This review discusses the history, traditional production process, philosophy, nutritional aspects, and different varieties of Pempek.